Myanmar Agricultural Performance Survey Round Three: Note on Sample Characteristics and Weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
The Myanmar Agricultural Performance Survey (MAPS) Round 3 provides nationally and sub-nationally representative data on agricultural performance, integrating insights from 4,892 farming households. Conducted between January and March 2023, this survey leverages phone-based data collection to address logistical challenges posed by Myanmar's remote and conflict-affected regions. MAPS modules encompass critical agricultural indicators, including crop production, marketing, input usage, farm assets, and services. The survey design integrates rigorous sampling and weighting strategies to ensure representation across demographic and geographical strata. Findings highlight variations in agricultural practices between seasons and years, alongside challenges in household retention due to conflict and infrastructure limitations. Despite attrition and inherent limitations of phone surveys, MAPS successfully enumerated 271 out of 324 townships, contributing vital data for understanding agricultural dynamics in Myanmar.